2005
DOI: 10.1017/s0031182004007127
|View full text |Cite
|
Sign up to set email alerts
|

Anoplocephala perfoliataof horses – significant scope for further research, improved diagnosis and control

Abstract: Anoplocephala perfoliata is the commonest tapeworm parasite of horses and is incriminated as a significant cause of clinical disease (e.g., ileocaecal intussusception, caeco-caecal intussusception and/or caecal perforation), particularly in horses chronically infected with large numbers of worms. The high prevalence (approximately 20-80%) of the parasite in some countries suggests an increased risk of clinical cases. In spite of research, there is still a paucity of information regarding the pathogenesis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 65 publications
4
41
0
Order By: Relevance
“…These relationships also confirmed by others (Gasser et al 2005; Traversa et al 2008) may explain varying effectiveness of coproscopic techniques during the invasion of tapeworms in horses. Another important factor that determines the efficacy of the coproscopic techniques is the weight of analyzed samples, which is relatively small (2 to 3 g) in the McMaster, flotation, and sedimentation techniques.…”
Section: Discussionsupporting
confidence: 78%
“…These relationships also confirmed by others (Gasser et al 2005; Traversa et al 2008) may explain varying effectiveness of coproscopic techniques during the invasion of tapeworms in horses. Another important factor that determines the efficacy of the coproscopic techniques is the weight of analyzed samples, which is relatively small (2 to 3 g) in the McMaster, flotation, and sedimentation techniques.…”
Section: Discussionsupporting
confidence: 78%
“…This virus effect could be either a direct effect of the physiological cost of infection, or an indirect effect of the increased superparasitism in infected parasitoids, as suggested by a previous study [50]. Indeed, virus-infected parasitoids are expected to develop more frequently in superparasitized larvae and must cope with intense competition.…”
Section: Discussionmentioning
confidence: 76%
“…Earlier, it was reported that A. magna and A. mamillana as the most common tapeworm while A. perfoliata as a rare species in horses (Olsen, 1938). However, recent studies report that A. perfoliata as the dominant equine tapeworm worldwide (Gasser et al, 2005). Among the trematodes, Fasciola hepatica and Dicrocoelium dentriticum are recorded in horses with relatively low infections (Brucknell et al, 1995).…”
Section: Amongmentioning
confidence: 99%